Areas for improvement in community optometry: flashes and floaters take priority. (19th June 2018) - Duncan, Eilidh M.; Cassie, Heather; Pooley, Janet; Elouafakoui, Paula; Prior, Maria; Gibb, Elizabeth; Ramsay, Craig; Young, Linda
Abstract: Purpose: A common response to rising demand for healthcare is to extend the role of health professionals and the range of their service provision. Community optometry in Scotland is a recent example of this. Within this context of innovation and change there are challenges to ensuring quality in optometry practice. The purpose of this research is to establish what the priorities are for practice improvement within community optometry and to start a programme to inform strategies to improve practice. Methods: A four stage study was conducted: (1) a service‐driven topic prioritisation exercise to identify priorities for optometry practice improvement; (2) a review of national and international guidance and UK protocols relating to the identified priority topic; (3) a national theory‐based survey identifying current practice and the barriers and facilitators to the target behaviour; and (4) the identification of theory‐based intervention options to improve practice. The Behaviour Change Wheel approach to behaviour change intervention development and Theoretical Domains Framework (TDF) provided the underlying theoretical framework. Results: Stakeholders identified 'patients presenting with flashes and floaters' as an important priority for practice improvement. The decision about whether or not to refer patients on to secondary care for further examination is the target behaviour. Guidance for optometrists on this topic is lacking. Six TDF domains were related to the decision about whether or not to refer patients with flashes and floaters to secondary care – 'social influences', 'emotion', 'beliefs about capabilities', 'beliefs about consequences', 'behavioural regulation' and 'reinforcement'. Conclusions: This study has examined current practice in relation to the management of patients with flashes and floaters, identified the most salient targets for future strategies to improve optometry practice and highlighted what form these strategies may take. It demonstrates the use of a flexible, theory‐informed approach, which can be used to engage with stakeholders and professionals to inform the design and development of efforts to improve practice in a variety of healthcare settings.